2020
DOI: 10.1177/1129729820978124
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and medical cost of peripheral intravenous catheter-related complications in hospitalised adult patients

Abstract: Background: Peripheral intravenous catheters (PVCs) are widely used vascular access devices for infusion therapy; however, they are associated with relatively high failure rates. This study aimed to identify the incidence, risk factors and medical costs of PVC-induced complications in adult hospitalised adult patients in China. Methods: An observational, prospective study on 1069 patients lasting 5 months was conducted at a tertiary teaching hospital. Results: Infiltration ranked first among PVC complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
38
1
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 36 publications
9
38
1
11
Order By: Relevance
“…However, in the present study peripheral catheters left in for over 96 hours did not show a higher incidence of complications. This finding was in line with a study's findings in China and King Abdulaziz Medical City, Riyadh, Saudi Arabia where duration for PIVCs insertion was not a significant predictor of the complications [ 10 ]. This was in agreement with the notion that routine replacement of PIVCs does not affect on the incidence of catheter failures [ 24 ] and the catheter for adult patients should be changed when clinically indicated only [ 16 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, in the present study peripheral catheters left in for over 96 hours did not show a higher incidence of complications. This finding was in line with a study's findings in China and King Abdulaziz Medical City, Riyadh, Saudi Arabia where duration for PIVCs insertion was not a significant predictor of the complications [ 10 ]. This was in agreement with the notion that routine replacement of PIVCs does not affect on the incidence of catheter failures [ 24 ] and the catheter for adult patients should be changed when clinically indicated only [ 16 ].…”
Section: Resultssupporting
confidence: 91%
“…e current study indicated that the majority of the complications were grade −1 in both phlebitis and infiltration. is finding is in line with the study finding in China where most of the complications in phlebitis (88.4%) and infiltration (93.7%) were grade −1 (10). It is also supported by a study conducted in Japan where 72.6% of phlebitis was Grade −1 [14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We therefore estimated them on the basis of series of observations in our hospital. Average costs to handle one episode of diffusion (€4.09 vs [€0.12-€19.41]), occlusion (€3.67 vs [€0.25-€14.03]) and phlebitis (€12.27 vs [€0.04-€14.49]) were in the range of values reported in China [ 21 ].…”
Section: Discussionmentioning
confidence: 98%
“…Numerous complications associated with the use of central venous catheters (CVCs) have been described in literature, including infections, leakage, and catheter-related thrombosis (CRT). 1,2 Besides morbidity and mortality resulting from the catheter-associated complication itself, catheter dysfunction may necessitate treatment interruption, negatively affecting the treatment outcome. 3 Different studies showed that complete or partial catheter occlusion affects 16-58% of patients after two years of CVC placement.…”
Section: Introductionmentioning
confidence: 99%